Gender Differences in Semantic Fluency Patterns in Children - Soriano, Federico Gonzalo (2016)
Previous literature in cognitive psychology has provided data involvingdifferences in language processing between men and women. It has been found that women areusually more proficient with certain semantic categories such as fruit, vegetables and furniture.Men are reported to be better at other categories semantic, e.g. tools and transport. The aim of thisarticle is to provide an inquiry about possible differences in semantic category processing of livingthings (LT) and inanimate objects (IO) by Argentinian Spanish-speakers school-aged children.The group of 86 children between 8 and 12 years old (51.16 % boys) has been assessed on asemantic fluency task. Six semantic categories have been tested, three of them from the LTdomain (animals, fruit/vegetables, and body parts) and three from the IO domain (transport,clothes and musical instruments). Results showed differences in semantic processing betweenboys and girls. Girls retrieved more items from the LT domain and activated more animals andfruit/vegetables. These findings appear to support an innate conceptual organization of the mind,which is presumably influenced by cultural factors and/or schooling.